Experimental hut evaluation of DawaPlus 3.0 LN and DawaPlus 4.0 LN treated with deltamethrin and PBO against free-flying populations of Anopheles gambiae s.l. in Vallée du Kou, Burkina Faso. - Koama Bayili; Sévérin N'Do; Rajpal S Yadav; Moussa Namountougou; Abdoulaye Ouattara; Roch K Dabiré; Georges A Ouédraogo; Abdoulaye Diabaté (PLoS ONE)
Background In view of widespread pyrethroid resistance in malaria vectors in Africa, two long-lasting insecticidal nets (LLINs) incorporated with a synergist, piperonyl butoxide (PBO), DawaPlus 3.0 (deltamethrin + PBO in the roof panel; deltamethrin alone in the side panels) and DawaPlus 4.0 (deltamethrin + PBO in all panels), were evaluated in an experimental hut trial in a rice growing irrigated area in Burkina Faso. Efficacy of nets was tested against free-flying malaria vector, Anopheles gambiae s.l., with high pyrethroid resistance involving L1014F kdr and CYP6P3P450 resistance mechanisms. Methodology The efficacy of unwashed and 20-times washed DawaPlus 3.0 (polyethylene roof panel with 120 mg/m2 deltamethrin and 440 mg/m2 PBO; polyester side panels with deltamethrin 100 mg/m2) and DawaPlus 4.0 (same composition as roof of DawaPlus 3.0) was evaluated against DawaPlus 2.0 (80 mg/m2 deltamethrin; positive control). Volunteer sleepers and treatments were rotated in huts using a Latin square design on 63 consecutive nights during August-October 2016. Mortality, human blood-feeding inhibition, deterrence and exit rates of An. gambiae s.l. were monitored. Principal findings Significantly higher rates of mortality and blood-feeding inhibition were observed with unwashed DawaPlus 4.0 (36%; 47.5%) than unwashed DawaPlus 3.0 (11.8%; 33.3%), DawaPlus 2.0 (4.3%; 6.4%) or untreated net (P < 0.05). Washing reduced personal protective efficacy yet PBO-LLINs were more protective and both met the WHO criteria. Conclusions The PBO-containing DawaPlus 4.0 significantly protected against An. gambiae s.l. in the study area. Unwashed DawaPlus 3.0 gave low to moderate protection against the positive control. PBO inhibits oxidase action; hence in areas with active malaria transmission having oxidase mechanisms, PBO nets could confer additional personal protection.